WHAT DRIVES BANK MUAMALAT INDONESIA'S PROFIT? AN INTERVENING ANALYSIS WITH NON-PERFORMING FINANCING VARIABLE - Murtadha, Muhammad Aziz; Pimada, Laila Masruro (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
Bank Muamalat Indonesia, the first Islamic bank in Indonesia, experienced a major problem: the high number of non-performing financing ratios. Increased problematic financing can lead to a decrease in profitability. Thus, the formulated purpose of this research is to see the condition of the increasing non-performing financing ratio in mediating the effect of the financial and macroeconomic performance ratio variables on the decline in profitability. This study used quarterly data on CAR, FDR, inflation, BI interest rates, NPF, and ROA of Bank Muamalat Indonesia from 2013 - 2020. Path analysis was used as the analysis tool. The results of this study indicate that FDR has a significant positive effect. NPF significantly negatively affects ROA, and CAR, inflation, and BI interest rates do not affect ROA. In addition, CAR has a significant negative effect on NPF, BI interest rates have a significant positive effect on NPF, and FDR and BI interest rates do not affect NPF. Meanwhile, the NPF variable can mediate the effect of CAR on ROA. Meanwhile, the NPF could not mediate the effect of FDR, inflation, and BI interest rates on ROA. It is expected that Bank Muamalat Indonesia will conduct periodic and comprehensive reviews with increasingly stringent financing selective, measurable planning in investment management, and restructuring of non-performing financing so that financial performance will improve.